2010
DOI: 10.1007/s00531-010-0583-5
|View full text |Cite
|
Sign up to set email alerts
|

Listric versus planar normal fault geometry: an example from the Eisenstadt-Sopron Basin (E Austria)

Abstract: In a gravel pit at the eastern margin of the Eisenstadt-Sopron Basin, a satellite of Vienna Basin (Austria), Neogene sediments are exposed in the hanging wall of a major normal fault. The anticlinal structure and associated conjugated secondary normal faults were previously interpreted as a rollover anticline above a listric normal fault. The spatial orientation and distribution of sedimentary horizons and crosscutting faults were mapped in detail on a laser scan of the outcrop wall. Subsequently, in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 46 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…A listric fault usually flattens downwards (Shelton 1984;Spahić et al 2011) with a low-angle plane lying on a (as often assumed) undeformed basement (Mauduit & Brun 1998). Even if listric faults are more common in extensional environments (Maloney et al 2012), they can also occur in compressional regimes (Groshong 2006).…”
Section: Listric Faultsmentioning
confidence: 99%
“…A listric fault usually flattens downwards (Shelton 1984;Spahić et al 2011) with a low-angle plane lying on a (as often assumed) undeformed basement (Mauduit & Brun 1998). Even if listric faults are more common in extensional environments (Maloney et al 2012), they can also occur in compressional regimes (Groshong 2006).…”
Section: Listric Faultsmentioning
confidence: 99%
“…For this study a sampling site was found in a gravel pit south of St. Margarethen (Burgenland, Austria). The outcrop is located at the eastern margin of the Neogene Eisenstadt-Sopron Basin [18,19] , a satellite basin of the Vienna Basin [20] , and exposes deltaic gravel of Miocene age (11.9–11.6 Ma) [14] . The gravel is mainly composed of limestone pebbles (85%), but dolomite (5%), sandstone (5%) and quartz (5%) pebbles, also occur.…”
Section: Sample Materials and Point-load Test Statisticsmentioning
confidence: 99%
“…Therefore, the characterization of active faults is one of the most important research topics in geophysics. For this purpose, various geophysical prospecting methods such as electrical resistivity (Arjwech et al., 2021), gravity (Hiramatsu et al., 2019), magnetic (Khalil, 2016), electromagnetic (Martí et al., 2020), self‐potential (Saribudak & Hauwert, 2017), and ground‐penetrating radar (Dujardin et al., 2014) are commonly used (Spahić et al., 2010). The magnetic method measures variations in the Earth's magnetic field caused by changes in the magnetic properties of the rocks.…”
Section: Introductionmentioning
confidence: 99%